2013
DOI: 10.1016/s1474-4422(13)70159-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dronabinol on progression in progressive multiple sclerosis (CUPID): a randomised, placebo-controlled trial

Abstract: SummaryBackgroundLaboratory evidence has shown that cannabinoids might have a neuroprotective action. We investigated whether oral dronabinol (Δ9-tetrahydrocannabinol) might slow the course of progressive multiple sclerosis.MethodsIn this multicentre, parallel, randomised, double-blind, placebo-controlled study, we recruited patients aged 18–65 years with primary or secondary progressive multiple sclerosis from 27 UK neurology or rehabilitation departments. Patients were randomly assigned (2:1) to receive dron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 19 publications
1
77
0
Order By: Relevance
“…Although it been suggested that the influence of CBD on CB 1 R-mediated effects of Δ9-THC are of marginal significance at the concentrations of CBD in typical US of smoked marijuana (Varvel et al 2006), it may be relevant that long-term follow-up in symptom-control trials suggested that oral Δ9-THC but not oral 1:1 CBD:Δ9-THC cannabis extracts (Cannador) containing comparable levels of Δ9-THC, could limit the accumulation of disabilities in MS ). This would be consistent with a neuroprotective effect of Δ9-THC (Carroll et al 2012), which was formally investigated in a recent trial in MS (Zajicek et al 2013).…”
Section: Lack Of Marked Immunosuppressive Effects Of Cannabinoids In Eaesupporting
confidence: 76%
See 1 more Smart Citation
“…Although it been suggested that the influence of CBD on CB 1 R-mediated effects of Δ9-THC are of marginal significance at the concentrations of CBD in typical US of smoked marijuana (Varvel et al 2006), it may be relevant that long-term follow-up in symptom-control trials suggested that oral Δ9-THC but not oral 1:1 CBD:Δ9-THC cannabis extracts (Cannador) containing comparable levels of Δ9-THC, could limit the accumulation of disabilities in MS ). This would be consistent with a neuroprotective effect of Δ9-THC (Carroll et al 2012), which was formally investigated in a recent trial in MS (Zajicek et al 2013).…”
Section: Lack Of Marked Immunosuppressive Effects Of Cannabinoids In Eaesupporting
confidence: 76%
“…This suggests that agonism of the CB 1 R by exogenous delivered cannabinoids should have neuroprotective potential. However, unfortunately, it was reported that daily treatment with oral Δ9-THC had no overall effect on the progression of MS in the progressive phase of MS (Zajicek et al 2013. Fig.…”
Section: Cannabinoids For the Control Of Progression In Multiple Sclementioning
confidence: 96%
“…However, to date, there are no clinical studies evaluating Sativex as a disease-modifying agent of progressive MS. The closest clinical study is the CUPID trial, the results of which were recently published (Zajicek et al, 2013). This study showed that dronabinol (Δ 9 -THC) administration to patients with progressive MS did not slow the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A brief overview on the important role of endocannabinoid signaling in a few CNS disorders is discussed below. trial failed to show benefits of dronabinol on multiple sclerosis progression, perhaps due to slow progression rate which confounded statistical detection of group differences (Zajicek et al 2013). …”
Section: Painmentioning
confidence: 99%